PENGARUH EDUKASI MEDIA GAMIFIKASI TENTANG MENARCHE TERHADAP KESIAPAN REMAJA PUTRI PRAPUBERTAS DI SDN PASIRLUHUR KABUPATEN BANDUNG - Dara Ayunda; Dian Purnama Sari; Melati Yuliandari; Haidir Syafrullah (Jurnal Sehat Masada, 2026)
Adolescent girls experience menarche as a sign of early puberty, but many are not yet physically, psychologically, socially, and cognitively prepared. SDKI data shows the average age of menarche is 13–14 years. A study at Pasirluhur Elementary School shows that 87% of female students are unprepared. Unpreparedness can lead to anxiety, dysmenorrhea, and unhealthy behaviors. Early education is important so that adolescents are emotionally ready and can maintain reproductive health. Gamification media serves as an interesting, interactive, and easily understood educational alternative for children of prepubertal age. This study aims to determine the influence of gamification media education about menarche on the readiness of prepubertal girls in Pasirluhur Elementary School, Bandung Regency. The method used in this study was a quantitative approach with a pre-experimental design, namely a pretest-posttest one group. A sample of 79 people was taken using total sampling, with 79 respondents. The results showed that before the intervention, 8.9% of students were prepared, while after the intervention, this percentage increased to 97.5%. Data analysis used the Wilcoxon Signed Rank test, showing a p value of 0.000 with a significance level of 0.05. The results of this study indicate a p value of 0.000 with a significance level of 0.05. Based on the research findings, it can be concluded that there is an impact on students' preparedness after being provided education through gamification media about menarche.